Corporate social responsibility in India - Sekhar, K.; Praseeda, C. (2006)
Corporate social responsibility (CSR) has emerged as an important concern in the wake of the ascendancy of market economy. India, with higher incidence of poverty, underutilization of human resources, skewed development, strained resource base and low sensitization level needs the intervention of all the institutions, including big business. In this process, the corporate sector, which expanded phenomenally due to economic liberalization policies, is expected to function in time with the society's norms and standards and the law of the land. Against this background, this paper attempts to focus on the state of CSR in India, and discusses the various strands of thought on it. In addition, the impending consequences of the penetration of big business into key-areas and measures for the implementation of best practices by the corporate world are also discussed. - Reproduced.
Keywords: Social responsibility - India; Social responsibility